“Sua Santità spera dunque fermamente che la Russia risorgerà”: The Newly Discovered Letter of Vyacheslav I. Ivanov from 1938 - Andrey B. Chichkin (Studia Litterarum)
Andrei Chichkin’s article is based on a number of archival documents. It details the episode that was important for Vyacheslav Ivanov (1866–1949), a conversation Russian poet had during a private audience in Rome with the head of the Catholic Church, Pope Pius XI on March 4, 1938. Pontiff’s special interest in Russia and Russian culture was manifested through the exhibition “Visions of Old Russia” by L. Brailovsky (Vatican, February 1935), initiated by the Рope himself. Prior to the meeting between the head of the Catholic Church and Vyacheslav Ivanov, the Rector of the Pontificium Collegium Russicum F. de Regis S. J. wrote a letter to Pius XI in which he informed the Рope about Ivanov’ work at Russicum as a professor of the Church Slavonic Language and about poet’s narrative work in progress “The Tale of Svetomir Tsarevich”. According to F. de Regis’ letter, Ivanov’s “Tale” expanded on the philosophical ideas of Vladimir Solovyov’s book “Russia and the Ecumenical Church”. One may assume that Solovyov’s philosophical legacy and Russia’s future were among the topics discussed between the Pontiff and the poet. Vyacheslav Ivanov’s own letter, which is published here for the first time, contains a detailed account of what really occurred during their conversation. This document is compared with another source — a testimony by Olga Shor, poet’s secretary and posthumous biographer. Chichkin’s article questions the correctness of Schor’s account. A number of unpublished archival documents referred to in this article deserve better attention from the scholars of Russian literature.